2018
DOI: 10.1017/ice.2017.320
|View full text |Cite
|
Sign up to set email alerts
|

To Be a CLABSI or Not to Be a CLABSI—That is the Question: The Epidemiology of BSI in a Large ECMO Population

Abstract: wanted to learn more about their role in stewardship, and identified venues to receive this education. Nurses with master's degrees were less likely to believe that nurses might play a role in ASPs, perhaps due to greater familiarity with the current state of ASP, and perhaps, therefore, they were less likely to think "outside the box" regarding a nursing role. Nonetheless, most nurses felt that they played a role in antimicrobial stewardship. The strengths of this study include the large number of nursing res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Our organism profile is similar to that reported in ECMO patients 1,2,4,6 . Amongst VV‐ECMO, common isolates include gram negative rods, candida species, and Staphylococcus/Streptococcus species 2,7,8 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our organism profile is similar to that reported in ECMO patients 1,2,4,6 . Amongst VV‐ECMO, common isolates include gram negative rods, candida species, and Staphylococcus/Streptococcus species 2,7,8 .…”
Section: Discussionsupporting
confidence: 81%
“…Our organism profile is similar to that reported in ECMO patients. 1,2,4,6 Amongst VV-ECMO, common isolates include gram negative rods, candida species, and Staphylococcus/Streptococcus species. 2,7,8 Compared to central venous catheter associated infections, the ECMO population microbiological spectrum shifts toward gram-negatives and fungi rather than Staphylococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the total hospital expenses for patients among ECMO infection group and ECMO non infection group were This may be linked with the following reasons. Firstly, nosocomial infection in patients supported by ECMO is highly likely to result in the death, which can cause significant underestimation of the hospital expenses due to nosocomial infection (28). Secondly, some studies have found that prophylactic antibiotics during ECMO could reduce nosocomial infection and showed lower mortality (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence density of ECMO-CLABSI was 10.54 per 1,000 ECMO days, which is in line with other observational studies. 3,4 Respiratory ECMO use has increased since the COVID-19 pandemic began, and increasing incidence density of ECMO-CLABSI has also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…2 Implicit in our perception of the problem is the assumption that it is getting inexorably worse. 3 Hospitals are seen as overcrowded, unsanitary facilities full of vulnerable patients and contaminated equipment where intense antimicrobial exposure drives the evolution of resistance. 4 Periodic updates catalog the various organisms that threaten our pharmaceutical armamentarium for any given year.…”
Section: Discussionmentioning
confidence: 99%